Multidisciplinary Collaboration Between Nurses and Physiotherapists: Enhancing Patient Recovery Outcomes - Alsubhi, Nabil Homid; Alshomrani, Mohammed Hamed; Ghazwani, Norah Ahmed Yahya; Sawadi, Fatimah Yahya Othman; Alshehri, Rawan Faez; Sanawi, Matarh Ahmed Hadi (Journal of Posthumanism, 2024)
This paper explores the synergistic collaboration between nurses and physiotherapists, two professions with distinct yet complementary roles in patient recovery. It traces the evolution of interprofessional teamwork from siloed practices to integrated models, examining practical models in acute care, specialized rehabilitation, and community settings. The paper evaluates the impact of this synergy on key patient outcomes, confirming that effective nurse-physiotherapist collaboration is associated with enhanced functional mobility, accelerated patient independence, reduced hospital length of stay and readmission rates, more effective pain management, and improved patient satisfaction. The paper also discusses strategies to overcome common barriers and foster a sustainable culture of collaboration, including interprofessional education, the development of integrated care pathways, and the cultivation of organizational support systems. The paper concludes that the integration of nursing and physiotherapy expertise is essential for optimizing patient recovery and advancing modern healthcare delivery.